2022
DOI: 10.4142/jvs.22018
|View full text |Cite
|
Sign up to set email alerts
|

Hepatotoxic mechanism of diclofenac sodium on broiler chicken revealed by iTRAQ-based proteomics analysis

Abstract: Background At the therapeutic doses, diclofenac sodium (DFS) has few toxic side effects on mammals. On the other hand, DFS exhibits potent toxicity against birds and the mechanisms remain ambiguous. Objectives This paper was designed to probe the toxicity of DFS exposure on the hepatic proteome of broiler chickens. Methods Twenty 30-day-old broiler chickens were randomized evenly into two groups (n = 10). DFS was administered orally at 10 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Apoptosis (programmed cell death) is a universal form of death regulated by genes, which is crucial for normal organismal development and homeostasis [50]. Research has indicated that the hepatotoxicity of diclofenac sodium (DFS) may be achieved by inducing hepatocyte apoptosis through the endoplasmic reticulum pathway [38]. In our work, some of the up-and down-regulated DPPs were enriched in apoptosis and protein processing in endoplasmic reticulum KEGG pathways.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Apoptosis (programmed cell death) is a universal form of death regulated by genes, which is crucial for normal organismal development and homeostasis [50]. Research has indicated that the hepatotoxicity of diclofenac sodium (DFS) may be achieved by inducing hepatocyte apoptosis through the endoplasmic reticulum pathway [38]. In our work, some of the up-and down-regulated DPPs were enriched in apoptosis and protein processing in endoplasmic reticulum KEGG pathways.…”
Section: Discussionmentioning
confidence: 68%
“…Retinol, a fat-soluble vitamin, is converted to retinaldehyde and retinoic acid in the liver to maintain the normal physiological functions, such as growth, vision, immunity, and antioxidation [36,37]. Retinol and its derivatives can improve the capabilities of antioxidation and scavenging free radicals to reduce the risk of inflammation and oxidative stress [38]. The extracellular matrix (ECM) is a part of the connective tissue layers surrounding muscle fibers.…”
Section: Discussionmentioning
confidence: 99%
“…The hepatic metabolism of diclofenac sodium results in the development of hepatic disorders (Jeon et al, 2021). By inhibiting cyclooxygenase, diclofenac sodium hinders the biological synthesis of prostaglandin from arachidonic acid; this activity impacts physiological functions including osmoregulation, reproduction, water transport, and immune defense in organisms (Sun et al, 2022). Furthermore, chronic and acute toxicity of diclofenac have detrimental effects on marine life, disrupting their regular physiological processes such as nutrition, reproduction, swimming, development, and growth, ultimately threatening their survival.…”
mentioning
confidence: 99%